Removal of Maxilon Golden Yellow GL EC 400% from the Wastewater by Adsorption Method Using Different Clays - Sevgi Güneş Durak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study was to evaluate the adsorption capability of clay minerals of halloysite, bentonite, kaolinite and natural clay (obtained from the Avanos) to remove Maxilon Golden Yellow GL EC 400% (MGY400) from aqueous solution. Different amounts of adsorbents (0.5, 1.0, 1.5 and 2.0 g.) were taken from the samples and according to the results obtained the most color removal clay material and adsorbent amount was found. Adsorption was applied on all clays at 25 oC temperature, 200 rpm mixing speed and different contact times (2, 5, 10, 20, 30, 40, 50, 60 min) in the batch reactor. Bentonite provided the highest dyestuff removal. Therefore, the second phase adsorption was continued with bentonite. The adsorption with bentonite were performed at different temperature (13 oC, 25 oC, 50 oC) and pH values (2, 4, 6, 8, 10, 12). When the pH was 12 and the temperature was 25 oC, it was determined that the removal rate of the dyestuff of bentonite reached up to 99.7%. According to the results, adsorption kinetics and isotherms were investigated, and evaluation was made for working conditions.